Praññʻ sūʹ vanʻ thamʻʺ sāʺ sa mīʺ myāʺ suiʹ - Maung Maung, U, 1925- (Vanʻʺ Moʻ Ūʺ Cā pe Phranʻʹ khyī reʺ, 1987)
Reminiscences of a Burmese public administrator about public service life; narratives to his public servant sons and daughter.